An adaptive trajectory-based group message delivery protocol with detour support for vehicular networks. (2018) - Chiou, Guann-Long; Yang, Shun-Ren
To realise I2V group message delivery, some previously proposed protocols utilise the future trajectories of vehicles to deploy message delivery routes. However, we have noticed that none of these protocols consider that the destination vehicles may take unexpected detours, resulting in these vehicles no longer passing the rendezvous points. Thus, the detoured vehicles miss the messages stored on the rendezvous points. To address this issue, this paper designs tc-eTGMD, which aims to redeploy only the routes for the detour vehicles when the detour events happen. Moreover, this scheme can guarantee the reaction time and can offload the traffic while handling the detour events. The specific contributions of this paper are as follows: (1) we formally formulate the trajectory-based I2V group message delivery with the detour events problem; (2) we give a detailed design of tc-eTGMD protocol and (3) we conduct extensive simulation experiments to evaluate tc-eTGMD's message delivery performance.